2013
DOI: 10.1007/s00259-013-2593-6
|View full text |Cite
|
Sign up to set email alerts
|

How smart is peptide receptor radionuclide therapy of neuroendocrine tumors especially in the salvage setting? The clinician’s perspective

Abstract: In the recent past there has been a substantial growth in the understanding of cancer biology with a consequent opening of a Pandora's box of scientific knowledge and advance in the biological perception of the disease. Paradoxically, this indepth, sun-burst-like knowledge has fogged the several established management protocols rather than clearing the doubts. The 'knowledge' that the hitherto established and proven therapeutics do not only target cancer cells but also 'normal' cells has shifted the attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Another report showed that long PFS after the initial treatment with PRRT predicts a prolonged PFS after salvage therapy [51], and argued that PRRT with 177 Lu-octreotate in the retreatment setting is a safe and effective option in patients with metastatic GEP-NETs. For these reasons, retreatment seems a good option for patients who responded well after the initial cycles of PRRT [52]. This novel and important concept of salvage therapy of NET needs to be tested in large, prospective, and multi-center trials to contribute to evidencebased findings.…”
Section: Salvage Treatmentmentioning
confidence: 99%
“…Another report showed that long PFS after the initial treatment with PRRT predicts a prolonged PFS after salvage therapy [51], and argued that PRRT with 177 Lu-octreotate in the retreatment setting is a safe and effective option in patients with metastatic GEP-NETs. For these reasons, retreatment seems a good option for patients who responded well after the initial cycles of PRRT [52]. This novel and important concept of salvage therapy of NET needs to be tested in large, prospective, and multi-center trials to contribute to evidencebased findings.…”
Section: Salvage Treatmentmentioning
confidence: 99%
“…In fact, reported experiences vary widely in terms of number of cycles and injected activity in both treatment and retreatment settings. 26 – 30 …”
Section: Prrt Retreatment In Gep-net Patients a New Therapeutic Applmentioning
confidence: 99%
“…Of note, the recent Food and Drug Administration approval of the most commonly used theranostic twin 68 Ga-/ 177 Lu-DOTATATE will most likely lead to an increased initiation of SSTR-targeting peptide receptor radionuclide therapies (PRRT) all over the U.S. (6). As such, it is anticipated that endoradiotherapy for NEN will experience an increasing use (7,8). Accurate scan interpretation, however, is of utmost importance to triage patients for theranostic interventions (9), to guide the referring oncologist to handle challenging cases or to recommend appropriate work-up (e.g.…”
Section: Introductionmentioning
confidence: 99%